DA LEITURA DE MUNDO À LEITURA DA PALAVRA: Memória, Infância e Diversidades - ERIKA CARLA NOGUEIRA DA SILVA (2022)
ABSTRACT Children's literature has the fundamental function of forming the critical development of young readers, as well as building their personality, in addition to inserting a child in the universe of books, images, symbols and imagination; thus fostering the interpretation of the world. Indeed, a work Os beaks that I had: zoological memories (2004), by Sylvia Orthof, is a narrative aimed at children. Starring funny characters (who were part of the author's life), a representation of the work (with a mnemonic reinforcement) a part of Orthof's life. Produced under the strong influence of the dramatic genre, diegesis involves the small reader with attractive and playful images. Thus, anchoring on the epistemological assumptions of Antonio Candido (1972; 2011) about Literature and human formation, on the studies of Fanny Abramovich (1997), Nelly Novaes (2000) and Celso Junior de Ferrarezi (2017) about the constitution of Children's Literature, the objective of this research is to analyze a configuration of the characters in the narrative text The spouts I had: zoological memories (2004), by Sylvia Orthof, in order to understand the author's diegetic construction mode, as well as the understanding of their literariness and respect for diversity. Thus, this work proposes a reflection based on the contextualization that art is a fundamental instrument for the development / formation of the human being. Keywords: Children and Youth. Childhood. Reader